(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Utilizing graphene for an extensive variety of uses regularly requires fragile substance handling and functionalization. Here we initially report the amalgamation of graphene nanoflakes with carboxylic corrosive gatherings at the graphene edges from multi-divider carbon nanotube materials. Utilizing this material we at that point demonstrate that exceptionally responsive carboxylic anhydride bunches exist in unique harmony with the carboxylic acids in watery scattering. Warming in vacuum moves the balance as around 80% of the carboxylic corrosive gatherings change to the anhydrides. These new bits of knowledge into graphene science empower us to build up a straightforward, straight-forward concoction functionalisation convention for graphene making utilization of the anhydrides. The graphene nanoflakes were found to respond promptly with amine nucleophiles in fluid scattering to yield the relating amides. The new convention enables us to change the zetapotential of the graphene nanoflakes and to enliven the graphene edges with gold nanoparticles. Because of its straightforwardness, we anticipate that this methodology will discover far reaching use in the compound functionalisation of graphene and to empower new graphene-based applications.